Finding Appropriated Practice of the Pilgrimage Space: Ideological Contestation on the Sacred Site in Surowiti Gresik, East Java - Taufiqurrohim Taufiqurrohim (Ulumuna, 2019)
This paper examines how pesugihan (seeking wealth through spirit assistance) contests with pilgrimage discourse ideologically. In specific, to trace more about the grounds of the rise of contrary assumption of the pesugihan, this study focusses on how the ideological view, as the essential thinking of people, develops identity, practice, and its spirituality matter. The identity is constructed from the single view in responding to the phenomena and creating a sameness of collective joy created into the group, as Edith Turner examines about communitas and false communitas to see how the contestation is crystallized. Furthermore, this paper reviews the various pilgrimage practices to see how the communitas applied what they believe in the context of the pilgrimage. Lastly, it discusses how the visitors find their spirituality on pilgrimage, to see the reconciliation of the communitas conflict through gaze in visiting the pesugihan site. The paper argues that pesugihan is contested due to the contrary assumption of the practice rather than to see it as being religious with the traditional matter of context.